Magnetic heterogeneous visible light Fenton catalytic material as well as preparation method and application thereof

Through the preparation of magnetic heterogeneous visible light Fenton catalytic materials, co-precipitation assisted pyrolysis method is used to prepare γ-Fe2O3-Fe3C@C3N4 nanoparticles, which solve the problem of unstable and difficult recovery of traditional homogeneous Fenton catalysts under neutral or alkaline conditions, and achieve efficient catalytic degradation and excellent recovery capabilities.

CN119524907AActive Publication Date: 2025-02-28SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510105324.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Traditional homogeneous Fenton catalysts are unstable under neutral or alkaline conditions and are difficult to recover. The utilization efficiency of light and H2O2 is low, resulting in large iron sludge yield and high acid adjustment cost.

Method used

The preparation method of magnetic heterogeneous visible light Fenton catalytic material is adopted to prepare γ-Fe2O3-Fe3C@C3N4 nanoparticles by coprecipitation assisted pyrolysis method, and the design idea of ​​nano core-shell domain and electron buffer layer is used to improve the stability and recovery ability of the catalyst.

Benefits of technology

It achieves efficient catalytic degradation under neutral or alkaline conditions, has excellent recycling ability and long-term stability, can maintain a degradation efficiency of more than 90% in high-concentration phenol wastewater, and broadens the limitations of the traditional Fenton pH range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524907A_ABST
    Figure CN119524907A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a magnetic heterogeneous visible light Fenton catalytic material and a preparation method and application thereof.The preparation method at least comprises the following steps that S1, melamine, guanine and ferric nitrate nonahydrate are dissolved in a solvent to obtain a melamine solution, a guanine solution and a ferric nitrate nonahydrate solution; s2, stirring and mixing the guanine solution and the melamine solution, adding the mixture into the ferric nitrate nonahydrate solution for coprecipitation, filtering the precipitate, and performing vacuum drying to obtain a precursor substance; and S3, firing the precursor substance to obtain the catalyst. The catalytic material provided by the invention has magnetism and excellent recovery capacity, the degradation efficiency can reach 90% or above within 30 min in the treatment of high-concentration phenol wastewater, and compared with the traditional Fenton reaction, the pH application range is widened, the cyclic degradation stability is high, and the efficiency can still be maintained at 80% after the catalytic material is used and regenerated for 9 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a magnetic heterogeneous visible light Fenton catalytic material and a preparation method and application thereof. Background Art

[0002] Advanced oxidation processes (AOPs) are a treatment technology that uses active oxygen groups (including free radicals and non-free radical systems) to partially or completely degrade organic pollutants. They are particularly suitable for treating wastewater that is difficult to biodegrade or contains high concentrations of organic pollutants. Among this series of processes, the Fenton oxidation process has attracted much attention due to its significant characteristics. 2+ The reaction with H2O2 generates a large amount of OH free radicals, which effectively degrades organic pollutants. This method is not only simple to operate, fast in degradation speed and high in removal efficiency, but also can achieve complete mineralization of pollutants at normal temperature and pressure.

[0003] However, traditional homogeneous Fenton catalysts have many limitations, such as low efficiency in light and H2O2 utilization and only applicable to acidic environments. Under neutral or alkaline conditions, the catalyst is easily converted into iron-containing precipitates, resulting in problems such as large iron sludge production and high acid adjustment costs. On the other hand, although heterogeneous Fenton materials have overcome some of the defects of homogeneous catalysts to a certain extent, most heterogeneous materials are still difficult to recycle, have weak regeneration capabilities, and have low mass transfer efficiency. In particular, iron-based materials, their easy aggregation and deactivation characteristics seriously affect the long-term stability and service life of the catalyst.

[0004] Therefore, there is an urgent need for a new type of heterogeneous Fenton catalyst, which can not only effectively overcome the shortcomings of the traditional Fenton method, but also have high catalytic activity and excellent durability. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a magnetic heterogeneous visible light Fenton catalytic material, which comprises at least the following steps: S1, dissolving melamine, guanine and ferric nitrate nonahydrate in solvents to obtain a melamine solution, a guanine solution and a ferric nitrate nonahydrate solution respectively; S2, stirring and mixing the guanine solution and the melamine solution, and then adding them to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate and vacuum drying to obtain a precursor; S3. Burn the precursor material to obtain.

[0006] In one embodiment, the molar ratio of melamine to guanine is 1:(1-3).

[0007] In a preferred embodiment, the molar ratio of melamine to guanine is any one of 1:1, 1:2 and 1:3.

[0008] In a more preferred embodiment, the molar ratio of melamine to guanine is 1:2.

[0009] In one embodiment, the molar ratio of melamine, guanine and ferric nitrate nonahydrate is 1:(1-3):8.

[0010] In a preferred embodiment, the molar ratio of melamine, guanine and ferric nitrate nonahydrate is 1:2:8.

[0011] In one embodiment, the melamine solution in step S1 is obtained by dissolving melamine in ultrapure water; the guanine solution is obtained by dissolving guanine in ammonia water; and the ferric nitrate nonahydrate solution is obtained by dissolving ferric nitrate nonahydrate in ultrapure water.

[0012] In a preferred embodiment, the melamine solution in step S1 is obtained by dissolving melamine in 80 mL ultrapure water; the guanine solution is obtained by dissolving guanine in 80 mL ammonia water; and the ferric nitrate nonahydrate solution is obtained by dissolving ferric nitrate nonahydrate in 40 mL ultrapure water.

[0013] In a more preferred embodiment, the melamine solution in step S1 is obtained by dissolving 3.6 mM melamine in 80 mL ultrapure water; the guanine solution is obtained by dissolving 7.2 mM guanine in 80 mL ammonia water; and the ferric nitrate nonahydrate solution is obtained by dissolving 28.8 mM ferric nitrate nonahydrate in 40 mL ultrapure water.

[0014] In one embodiment, the mass fraction of the ammonia water is 2.5%.

[0015] In one embodiment, the dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature, and the rotation speed is 300-500 rpm, which can be 300 rpm, 400 rpm, or 500 rpm.

[0016] In a preferred embodiment, the dissolution in step S1 is performed by magnetic stirring after ultrasound at room temperature, with a rotation speed of 300 rpm.

[0017] In one embodiment, the stirring and mixing in step S2 is performed at a speed of 900 to 1500 rpm, which can be 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, or 1500 rpm.

[0018] In a preferred embodiment, the rotation speed of the stirring and mixing in step S2 is 1000 rpm.

[0019] In one embodiment, in step S2, ultrasonic treatment is performed after stirring and mixing.

[0020] In a preferred embodiment, the ultrasonic treatment conditions in step S2 are a power of 50-60 kHz and an ultrasonic time of 20-30 min.

[0021] In a more preferred embodiment, the conditions of ultrasonic treatment in step S2 are power of 53 kHz and ultrasonic time of 20 min.

[0022] In one embodiment, the vacuum drying conditions in step S2 are vacuum degree -0.05~-0.15 KPa, temperature 60~80°C, and time 12~15h.

[0023] In a preferred embodiment, the vacuum drying conditions in step S2 are vacuum degree -0.1 KPa, temperature 60°C, and time 12 h.

[0024] In one embodiment, the step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

[0025] In one embodiment, the step S3 is specifically as follows: burning the precursor material obtained in the step S2 in a tubular furnace whose atmosphere gas is nitrogen.

[0026] In one embodiment, the flow rate of nitrogen in step S3 is 0.3 L / min.

[0027] In a preferred embodiment, the S3 step is specifically as follows: placing the precursor obtained in the S2 step in a quartz boat equipped with a quartz cover and burning it in a tubular furnace with a nitrogen atmosphere gas, the nitrogen flow rate is 0.3L / min, the heating rate is 5°C / min, the temperature is raised to 550°C and kept for 4 hours, and the product is obtained.

[0028] A second aspect of the present invention provides a magnetic heterogeneous visible light Fenton catalytic material prepared according to the above preparation method.

[0029] In one embodiment, the magnetic heterogeneous visible light Fenton catalytic material is γ-Fe2O3-Fe3C@C3N4 nanoparticles.

[0030] In a preferred embodiment, the average particle size of the γ-Fe2O3-Fe3C@C3N4 nanoparticles is 60-90 nm.

[0031] A third aspect of the present invention provides an application of a magnetic heterogeneous visible light Fenton catalytic material for treating wastewater containing organic pollutants.

[0032] The present invention adopts the design concept of nano core-shell confinement and electronic buffer layer, which can protect the iron carbide and iron oxide phases, improve stability, and accelerate the separation of holes and photogenerated electrons and accelerate mass transfer, that is, during the degradation process, the oxidant first reacts with the carbon layer with surface carbon defects to reduce the deactivation degree of the iron phase, and then enters the core iron phase of the material through the pore structure on the core-shell surface. At the same time, due to the spatial limitation of the shell layer, the agglomeration effect of the nano iron phase is suppressed, and there are more Lewis acid sites inside the core-shell, and the activation rate of hydrogen peroxide at the Lewis acid sites is improved, thereby accelerating the charge separation process of the catalyst and increasing the density of transient photocurrent.

[0033] Beneficial Effects

[0034] 1. The present invention adopts a simple co-precipitation-assisted pyrolysis method to prepare a magnetic heterogeneous visible light Fenton catalytic material, which can protect the iron carbide and iron oxide phases, improve stability, and accelerate the separation of holes and photogenerated electrons and accelerate mass transfer.

[0035] 2. The catalytic material provided by the present invention has magnetism and excellent recovery ability. It maintains a degradation efficiency of more than 90% within 30 minutes in the treatment of high-concentration phenol wastewater, and broadens the limitations of the traditional Fenton pH range. After 9 times of regeneration, it still maintains an efficiency of 80%. At the same time, it also has beneficial photo-Fenton degradation performance for antibiotics and dye pollutants.

[0036] 3. The magnetic heterogeneous visible light Fenton catalytic material prepared by the present invention is composed of a γ-Fe2O3-Fe3C core and a C3N4 porous shell. Under the core-shell confinement, it not only hinders the agglomeration of nano-iron-based materials, but also allows pollutants to be confined inside the core-shell pores, accelerating the mass transfer reaction. The external carbon nitride layer with carbon defects can also act as an electronic buffer layer, reducing the oxidation of the internal active iron phase and improving the stability of the catalyst.

[0037] 4. The preparation method provided by the present invention has a simple process and does not require complicated equipment to prepare a magnetic heterogeneous visible light Fenton catalytic material with high catalytic activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a performance comparison chart of the catalytic degradation of phenol (100 ppm) by the magnetic heterogeneous visible light Fenton catalytic materials prepared in Examples 1-4; Figure 2 The kinetic curves of the removal of phenol (100 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1 in different reaction systems; Figure 3The degradation kinetic curve of tetracycline hydrochloride (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 4 The degradation kinetic curve of norfloxacin (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 5 The degradation kinetic curve of sulfamethoxazole (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 2-5 In, C t / C0 is used to quantitatively describe the residual proportion of reactants in the degradation process at t minutes. t represents the concentration of the reactant at t minutes, while C0 represents the concentration of the reactant at the initial moment; Figure 6 This is a test diagram of the pH applicable range of the magnetic heterogeneous visible light Fenton catalytic material prepared in Example 1; Figure 7 This is a test chart of the cyclic degradation stability of the magnetic heterogeneous visible light Fenton catalytic material prepared in Example 1 (each repetition time is 60 minutes). DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods for which specific conditions are not specified in the embodiments are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] A first aspect of the present embodiment provides a method for preparing a magnetic heterogeneous visible light Fenton catalytic material, comprising at least the following steps: S1, dissolving 3.6 mM melamine in 80 mL ultrapure water to obtain a melamine solution, dissolving 7.2 mM guanine in 80 mL ammonia water to obtain a guanine solution, and dissolving 28.8 mM ferric nitrate nonahydrate in 40 mL ultrapure water to obtain a ferric nitrate nonahydrate solution; the mass fraction of the ammonia water is 2.5%; S2, stirring and mixing the guanine solution and the melamine solution at a speed of 1000 rpm, subjecting the mixture to ultrasonic treatment at 53 kHz for 20 minutes, and then adding the mixture to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate, and vacuum drying to obtain a precursor substance; S3. Place the precursor obtained in step S2 in a quartz boat equipped with a quartz cover and burn it in a tubular furnace with a nitrogen atmosphere gas. The nitrogen flow rate is 0.3 L / min, the heating rate is 5°C / min, and the temperature is raised to 550°C and kept for 4 hours to obtain the product.

[0042] The dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature at a rotation speed of 300 rpm.

[0043] The vacuum drying conditions in step S2 are vacuum degree -0.1 KPa, temperature 60°C, and time 12 h.

[0044] The step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

[0045] The second aspect of this embodiment provides a magnetic heterogeneous visible light Fenton catalytic material prepared according to the above preparation method. The magnetic heterogeneous visible light Fenton catalytic material is γ-Fe2O3-Fe3C@C3N4 nanoparticles.

[0046] A third aspect of this embodiment provides an application of a magnetic heterogeneous visible light Fenton catalytic material for the treatment of wastewater with organic pollutants.

[0047] Figure 2 The kinetic curves of the removal of phenol (100 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1 in different reaction systems; Figure 3 The degradation kinetic curve of tetracycline hydrochloride (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 4 The degradation kinetic curve of norfloxacin (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 5 This is the degradation kinetic curve of sulfamethoxazole (50 ppm) by the magnetic heterogeneous visible light Fenton catalytic material of Example 1; Figure 2-5 In, C t / C0 is used to quantitatively describe the residual proportion of reactants in the degradation process at t minutes. t represents the concentration of the reactant at t minutes, while C0 represents the concentration of the reactant at the initial moment; Figure 6 This is a test diagram of the pH applicable range of the magnetic heterogeneous visible light Fenton catalytic material prepared in Example 1; Figure 7 This is a test chart of the cyclic degradation stability of the magnetic heterogeneous visible light Fenton catalytic material prepared in Example 1.

[0048] Example 2

[0049] A first aspect of the present embodiment provides a method for preparing a magnetic heterogeneous visible light Fenton catalytic material, comprising at least the following steps: S1, dissolving 3.6 mM melamine in 80 mL ultrapure water to obtain a melamine solution, dissolving 10.8 mM guanine in 80 mL ammonia water to obtain a guanine solution, and dissolving 28.8 mM ferric nitrate nonahydrate in 40 mL ultrapure water to obtain a ferric nitrate nonahydrate solution; the mass fraction of the ammonia water is 2.5%; S2, stirring and mixing the guanine solution and the melamine solution at a speed of 1000 rpm, subjecting the mixture to ultrasonic treatment at 53 kHz for 20 minutes, and then adding the mixture to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate, and vacuum drying to obtain a precursor substance; S3. Place the precursor obtained in step S2 in a quartz boat equipped with a quartz cover and burn it in a tubular furnace with a nitrogen atmosphere gas. The nitrogen flow rate is 0.3 L / min, the heating rate is 5°C / min, and the temperature is raised to 550°C and kept for 4 hours to obtain the product.

[0050] The dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature at a rotation speed of 300 rpm.

[0051] The vacuum drying conditions in step S2 are vacuum degree -0.1 KPa, temperature 60°C, and time 12 h.

[0052] The step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

[0053] The second aspect of this embodiment provides a magnetic heterogeneous visible light Fenton catalytic material prepared according to the above preparation method. The magnetic heterogeneous visible light Fenton catalytic material is γ-Fe2O3-Fe3C@C3N4 nanoparticles.

[0054] A third aspect of this embodiment provides an application of a magnetic heterogeneous visible light Fenton catalytic material for the treatment of wastewater with organic pollutants.

[0055] Example 3

[0056] A first aspect of the present embodiment provides a method for preparing a magnetic heterogeneous visible light Fenton catalytic material, comprising at least the following steps: S1, dissolving 3.6 mM melamine in 80 mL ultrapure water to obtain a melamine solution, dissolving 3.6 mM guanine in 80 mL ammonia water to obtain a guanine solution, and dissolving 28.8 mM ferric nitrate nonahydrate in 40 mL ultrapure water to obtain a ferric nitrate nonahydrate solution; the mass fraction of the ammonia water is 2.5%; S2, stirring and mixing the guanine solution and the melamine solution at a speed of 1000 rpm, subjecting the mixture to ultrasonic treatment at 53 kHz for 20 minutes, and then adding the mixture to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate, and vacuum drying to obtain a precursor substance; S3. Place the precursor obtained in step S2 in a quartz boat equipped with a quartz cover and burn it in a tubular furnace with a nitrogen atmosphere gas. The nitrogen flow rate is 0.3 L / min, the heating rate is 5°C / min, and the temperature is raised to 550°C and kept for 4 hours to obtain the product.

[0057] The dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature at a rotation speed of 300 rpm.

[0058] The vacuum drying conditions in step S2 are vacuum degree -0.1 KPa, temperature 60°C, and time 12 h.

[0059] The step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

[0060] The second aspect of this embodiment provides a magnetic heterogeneous visible light Fenton catalytic material prepared according to the above preparation method. The magnetic heterogeneous visible light Fenton catalytic material is γ-Fe2O3-Fe3C@C3N4 nanoparticles.

[0061] A third aspect of this embodiment provides an application of a magnetic heterogeneous visible light Fenton catalytic material for the treatment of wastewater with organic pollutants.

[0062] Example 4

[0063] A first aspect of the present embodiment provides a method for preparing a magnetic heterogeneous visible light Fenton catalytic material, comprising at least the following steps: S1, dissolving 3.6 mM melamine in 80 mL ultrapure water to obtain a melamine solution, dissolving 3.6 mM guanine in 80 mL ammonia water to obtain a guanine solution, and dissolving 28.8 mM ferric nitrate nonahydrate in 40 mL ultrapure water to obtain a ferric nitrate nonahydrate solution; the mass fraction of the ammonia water is 2.5%; S2, stirring and mixing the guanine solution and the melamine solution at a speed of 1000 rpm, subjecting the mixture to ultrasonic treatment at 53 kHz for 20 minutes, and then adding the mixture to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate, and vacuum drying to obtain a precursor substance; S3. Place the precursor obtained in step S2 in a quartz boat equipped with a quartz cover and burn it in a tube furnace with an air atmosphere. The flow rate of nitrogen is 0.3 L / min, the heating rate is 5°C / min, and the temperature is raised to 550°C and kept for 4 hours to obtain the product.

[0064] The dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature at a rotation speed of 300 rpm.

[0065] The vacuum drying conditions in step S2 are vacuum degree -0.1 KPa, temperature 60°C, and time 12 h.

[0066] The step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

[0067] The second aspect of this embodiment provides a magnetic heterogeneous visible light Fenton catalytic material prepared according to the above preparation method. The magnetic heterogeneous visible light Fenton catalytic material is γ-Fe2O3-Fe3C@C3N4 nanoparticles.

[0068] A third aspect of this embodiment provides an application of a magnetic heterogeneous visible light Fenton catalytic material for the treatment of wastewater with organic pollutants.

[0069] Figure 1 Comparison of catalytic performance of magnetic heterogeneous visible light Fenton catalytic materials prepared in Examples 1-4 Performance Testing 1. Photo-Fenton performance test: Test object: the magnetic heterogeneous visible light Fenton catalytic material samples prepared by Examples 1-4.

[0070] Test method: The degradation experiment was carried out in a photochemical reaction device, which includes two modules: a power trigger and a light source. The outer layer of the equipped double-layer quartz reactor (volume 150 mL) can be circulated with cooling water to inhibit the temperature rise of the system caused by light (maintaining the temperature at room temperature), and the following degradation experiment was carried out: before the reaction, 0.05g of sample was added to 100 mL of phenol (100 mg / L) solution, and it was quickly stirred in the dark for 30 min to achieve adsorption and desorption equilibrium. Then 1ml of H2O2 was added to the system, the light source (300 W xenon lamp with 420 nm UV filter) was turned on, and the cooling water was circulated to induce the photo-Fenton reaction. At this moment, the timing started, and 1-2 mL of the suspension was extracted with a syringe every 5 min, and the solid catalyst was filtered through a 0.22 μm filter head, stored in a 5 mL centrifuge tube and an excess of H2O2 was added to quench the remaining H2O2 in the enzyme quenching solution, and refrigerated in a refrigerator at 4°C. The concentration of phenol in the water sample to be tested, the above experiment was repeated in two groups. Unless otherwise specified, the initial pH of the solution was not adjusted to 6-7. Figure 1 .

[0071] from Figure 1It can be seen that the catalytic performance of the magnetic heterogeneous visible light Fenton catalytic material prepared by the present invention reaches more than 90%, and the efficiency of the catalyst prepared in the nitrogen atmosphere is increased by 28.2% compared with that prepared in the air atmosphere (Example 4), indicating that the low-valent iron phase in the core-shell structure can be better retained in the nitrogen atmosphere.

[0072] At the same time, the present invention also carried out photo-Fenton degradation of antibiotics and dye pollutants to test the removal effect of γ-Fe2O3-Fe3C@C3N4 on different pollutant substrates. The test method is the same as the test method in the above-mentioned photo-Fenton performance test, except that phenol is replaced by 50 ppm tetracycline hydrochloride, norfloxacin, and sulfamethoxazole, respectively. The test results are shown in Figure 2-5 It can be seen from the figure that the magnetic heterogeneous visible light Fenton catalytic material prepared by the present invention also has beneficial photo-Fenton degradation performance for antibiotics and dye pollutants.

[0073] 2. Photocatalytic synergistic Fenton removal effect test The present invention tests the phenol removal effect of the γ-Fe2O3-Fe3C@C3N4 catalytic material prepared in Example 1 under different reaction conditions (adsorption, photocatalysis, dark Fenton, photo-Fenton). The test method is as follows.

[0074] Adsorption test: 0.05 g of γ-Fe2O3-Fe3C@C3N4 material was placed in a sandwich beaker containing 100 mL of 100 mg / L phenol solution in the dark and mechanically stirred (speed of 170 rpm). 1-2 mL of the suspension was taken with a syringe at 0, 1, 3, 5, 7, 10, 20, 30, 40, 60, 70, 90 min, filtered through a 0.22 μm filter membrane, and placed in a 4 ° C refrigerator for testing.

[0075] Photocatalytic test: 0.05 g of γ-Fe2O3-Fe3C@C3N4 material was placed in a sandwich beaker containing 100 mL of 100 mg / L phenol solution in the dark and mechanically stirred for 30 min (speed 170 rpm). Immediately turn on the xenon lamp with a 420 nm filter (420-700 nm, 20k lux), and then turn on the cooling circulation pump (maintaining a room temperature of 25°C). Every 5 min, 1-2 mL of the suspension was extracted with a syringe, filtered through a 0.22 μm filter membrane, and placed in a 4°C refrigerator for testing.

[0076] Dark Fenton test: 0.05g of γ-Fe2O3-Fe3C@C3N4 material was placed in a sandwich beaker containing 100 mL of 100mg / L phenol solution in the dark, and mechanically stirred for 30 min (speed 170 rpm). Then 1mL of hydrogen peroxide solution was immediately added, and 1-2mL of the suspension was extracted with a syringe every 5 minutes, filtered through a 0.22μm filter membrane, stored in a 5mL centrifuge tube, and excess H2O2 was added to quench the remaining H2O2 in the enzyme solution.

[0077] Photo-Fenton test: 0.05 g of γ-Fe2O3-Fe3C@C3N4 material was placed in a sandwich beaker containing 100 mL of 100 mg / L phenol solution in the dark, and mechanically stirred for 30 min (speed 170 rpm). Immediately thereafter, 1 mL of hydrogen peroxide solution was added and a xenon lamp (420-700 nm, 20k lux) with a 420 nm filter was turned on at the same time, and then the cooling circulation pump was turned on (maintaining a room temperature of 25°C). 1-2 mL of the suspension was drawn out with a syringe every 5 min, filtered through a 0.22 μm filter membrane, stored in a 5 mL centrifuge tube, and excess H2O2 was added to quench the remaining H2O2 in the enzyme solution.

[0078] Test results see Figure 2 As can be seen from the figure, the degradation rate of phenol by the material can reach more than 90% under 30 min of visible light irradiation, indicating that there is a significant synergistic effect between the photocatalytic and Fenton oxidation processes.

[0079] 3. pH applicable range test: The test method in the above-mentioned photo-Fenton performance test was used, except that the pH was adjusted by a 0.1 mM NaOH or HCl dilute solution to explore the catalytic performance of the magnetic heterogeneous visible light Fenton catalytic material prepared in Example 1 under the condition of pH value of 1-11. The test results are shown in Figure 6 .

[0080] As can be seen from the figure, under acidic conditions (pH 1-6), the photo-Fenton efficiency is maintained at more than 90% in the pH range of 3-6, and under weakly alkaline conditions (pH 7-9), it is maintained at more than 80%. Under extremely alkaline conditions of 10-11, the efficiency is significantly reduced to 63% and 34%. It should be emphasized that the pH value of general phenol wastewater is weakly acidic. As the initial pH value of the solution is adjusted from 3 to 7, the solubility of the material decreases, resulting in a gradual increase in the adsorption rate of phenol by the material, which is more conducive to the removal of phenol. In summary, the pH application range of the material prepared in Example 1 is significantly expanded in the process of photo-Fenton degradation of phenol.

[0081] 4. Cyclic degradation stability test: like Figure 7 As shown, in order to evaluate the reusability of the magnetic heterogeneous visible light Fenton catalytic material prepared by the present invention under the same conditions, nine phenol degradation cycle experiments were carried out continuously. Since the γ-Fe2O3-Fe3C@C3N4 material prepared by the present invention has excellent strong magnetism, it can be directly recovered by magnet, rinsed with ethanol and ultrapure water, and dried for repeated use. After the first use and repeated use for 2 times, the efficiency of photo-Fenton degradation of phenol reached more than 95.5%; as the number of uses increased, the rate of photo-Fenton degradation of phenol decreased; but it could still maintain a phenol removal rate of nearly 80% at the 9th use. This shows that the material still has a strong ability to degrade phenol by photo-Fenton catalysis after multiple uses, and the strong magnetism gives the material the advantage of 100% recovery. Compared with traditional Fe-MOF and g-C3N4, the γ-Fe2O3-Fe3C@C3N4 material prepared by the present invention has excellent recyclability and strong stability, and is a potential heterogeneous Fenton catalyst.

[0082] in, Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 7 Middle: C t / C0 is used to quantitatively describe the residual proportion of reactants in the degradation process at t minutes, where C t refers to the concentration of the reactant at t minutes, while C0 refers to the concentration of the reactant at the initial moment.

Claims

1. A method for preparing a magnetic heterogeneous visible light Fenton catalytic material, characterized in that: At least the following steps are included: S1, dissolving melamine, guanine and ferric nitrate nonahydrate in solvents to obtain a melamine solution, a guanine solution and a ferric nitrate nonahydrate solution respectively; S2, stirring and mixing the guanine solution and the melamine solution, and then adding them to a nonahydrate ferric nitrate solution for co-precipitation, filtering the precipitate and vacuum drying to obtain a precursor; S3. Burn the precursor material to obtain.

2. The method for preparing the magnetic heterogeneous visible light Fenton catalytic material according to claim 1, characterized in that: The molar ratio of melamine to guanine is 1:(1-3).

3. The method for preparing the magnetic heterogeneous visible light Fenton catalytic material according to claim 1, characterized in that: In step S1, the melamine solution is obtained by dissolving melamine in ultrapure water; the guanine solution is obtained by dissolving guanine in ammonia water; and the ferric nitrate nonahydrate solution is obtained by dissolving ferric nitrate nonahydrate in ultrapure water.

4. The method for preparing a magnetic heterogeneous visible light Fenton catalytic material according to any one of claims 1 to 3, characterized in that: The dissolution in step S1 is performed by magnetic stirring after ultrasonication at room temperature, with a rotation speed of 300-500 rpm.

5. The method for preparing the magnetic heterogeneous visible light Fenton catalytic material according to claim 1, characterized in that: The stirring and mixing speed in the step S2 is 900-1500 rpm.

6. The method for preparing a magnetic heterogeneous visible light Fenton catalytic material according to claim 5, characterized in that: The vacuum drying conditions in step S2 are as follows: vacuum degree -0.05~-0.15 KPa, temperature 60~80°C, and time 12~15h.

7. The method for preparing a magnetic heterogeneous visible light Fenton catalytic material according to claim 1, characterized in that: The step S2 further comprises grinding the precursor material and then passing it through a 200-mesh sieve.

8. The method for preparing a magnetic heterogeneous visible light Fenton catalytic material according to claim 1, characterized in that: The step S3 specifically comprises: burning the precursor obtained in the step S2 in a tubular furnace whose atmosphere gas is nitrogen.

9. A magnetic heterogeneous visible light Fenton catalytic material prepared according to the preparation method according to any one of claims 1 to 8.

10. An application of the magnetic heterogeneous visible light Fenton catalytic material according to claim 9, characterized in that: Used in the treatment of wastewater containing organic pollutants.

Citation Information

Patent Citations

  • Preparation method and application of carbon nitride supported chromium monoatom Fenton catalyst

    CN109967112A

  • Device and method for realizing free radical targeted oxidation in heterogeneous Fenton oxidation process

    CN113060819A

  • Iron-based nano catalytic treatment reagent and preparation method and application thereof

    CN113980059A